Answer
The last line of the table is correct.
And option C is correct for the values of p and q.
p = -3
q = 4
p + q = 1
Step-by-step explanation
To solve this, the best approach is to solve this quadratic expression in order to obtain the value(s) of p and q.
x² + x - 12
= x² + 4x - 3x - 12
= x (x + 4) - 3 (x + 4)
= (x - 3) (x + 4)
Comparing this with(x + p) (x + q), we see what p and q are easily.
(x - 3) (x + 4)
(x + p) (x + q)
p = -3
q = 4
(p + q) = (-3 + 4) = 1
The last line of the table is correct.
And option C is correct for the values of p and q.
Hope this Helps!!!